Modification of counter recoil system in pneumatic counter-tank weapon (CTW) for recoil force reduction - Siti Duratun Nasiqiati Rosady; Transisma Budiarta; Satworo Adiwidodo; Asrori Asrori; Haris Puspito Buwono (Jurnal Polimesin, 2026)
The rapid advancement of defense technology within the Indonesian Army (TNI AD) requires effective, realistic training systems for Counter-Tank Weapons (CTW). Pneumatic CTW trainers have been developed as cost-effective alternatives to live-fire training; however, field tests indicate significant recoil that reduces weapon stability and shooter comfort. Unlike conventional recoil mitigation methods that rely on external dampers, springs, or structural reinforcement, this study proposes an integrated, collision-based counter-recoil mechanism embedded within the valve lever assembly that reduces recoil through internal momentum transfer without adding complex external components. This study aims to design and evaluate the proposed mechanism to reduce recoil force while maintaining firing accuracy and projectile range. Experimental tests were conducted at Politeknik Angkatan Darat under controlled conditions, using three pressure levels (10-30 bar) and three counter pad masses (0.5-1.5 kg), with three repetitions per condition. Recoil force was measured using a calibrated load cell sensor, while projectile range was recorded manually. Data were analyzed using two-way ANOVA to evaluate the effects of pressure and pad mass on recoil behavior. The results show that the proposed internal collision-based counter recoil system significantly reduced recoil force across all pressure levels. At 30 bar, recoil decreased from 81.7 N (without modification) to 65.7 N using a 0.5 kg pad and further decreased to 34.33 N with a 1.5 kg pad. Statistical analysis confirmed that both pressure and pad mass significantly influence recoil force (p 0.001, R² = 98.35%). In addition, the maximum firing range increased from 190.7 m to 221.7 m, indicating improved energy transfer and launcher stability. Although the 1.5 kg counterpad had the lowest recoil force, its additional mass may reduce launcher mobility and operator comfort. The 1.0 kg pad provides a balanced compromise between recoil reduction and ergonomic usability, making it more suitable for routine training applications. These findings demonstrate that the proposed internal collision-based counter recoil mechanism offers an effective, passive, lightweight, and practical solution for mitigating recoil in pneumatic CTW training launchers while preserving operational realism and ease of maintenance.